Production of protein hydrolysates from sea cucumber (Holothuroidea) innards by papain hydrolysis. - Ly, Tạ Ngọc; Anh, Nguyen Thi (Vietnam Journal of Science and Technology, 2022)
Sea cucumber innards (SCI) are the main waste of the sea cucumber processing industry. SCI protein hydrolysates were prepared using Papain and kinematic parameters of SCI-Papain hydrolysis reaction were studied. The hydrolysates were subsequently analyzed for their antioxidant potential and amino acid composition for the first time. The results showed that the highest degree of hydrolysis (DH) was achieved at an enzyme/substrate ratio of 0.06/75 (w/w) and a hydrolysis time of 180 mins. The kinematic parameters of SCI-Papain hydrolysis reaction were investigated using the Lineweaver-Burk model, which Km and Vmax were calculated to be 0.21 g/L and 1.69 mgN/min, respectively. SCI hydrolysates have high nutritional components when detecting 16/22 amino acids, including 8/9 essential amino acids. SCI hydrolysates with a DH of 15 % exhibited the highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, equal to 62.8 %. This finding suggested the potential of using SCI protein hydrolysates as therapeutic bioactive ingredients in functional food development.